Sirtuins in neurodegenerative diseases: an update on potential mechanisms - Min, Sang-won; Sohn, Peter D.; Cho, Seo-hyun; Swanson, Raymond A.; Gan, Li (Frontiers in Aging Neuroscience, 2013)
Silent information regulator 2 proteins (sirtuins or SIRTs) are a group of deacetylases (or deacylases) whose activities are dependent on and regulated by nicotinamide adenine dinucleotide (NAD+). Compelling evidence supports that sirtuins play major roles in many aspects of physiology, especially in pathways related to aging–the predominant and unifying risk factor for neurodegenerative diseases. The focus of this review is to examine the molecular mechanisms underlying the protective effects of sirtuins in neurodegenerative diseases, focusing on protein homeostasis, neural plasticity, mitochondrial function, and sustained chronic inflammation. We will also examine the potential and challenges of targeting sirtuin pathways to block these pathogenic pathways.